Representasi Budaya Melalui Simbol Pencak Silat di Tengah Masyarakat Multikultural - Septi Ayu Lestari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Language, art, and traditions in Indonesia remain alive and continue to develop. Pencak Silat is a highly renowned martial art that is widely practiced both domestically and internationally. This martial art carries cultural, moral, and spiritual values that have been passed down through generations. It is not merely a sport or a means of self-defense. Within the martial art of Pencak Silat, there are various symbols that hold deep and significant meanings. This research aims to determine the meanings of the symbols used in Pencak Silat in Indonesia. The study utilizes the concepts of intercultural communication and symbolic meaning theory to analyze the data gathered. The methodology employed in this research is a qualitative approach with a descriptive nature, using data collection techniques based on phenomenology. The data analysis techniques used in this study include direct observation and in-depth interviews with several informants who are actively involved in the practice of Pencak Silat. Based on the interviews, the researcher obtained information about the training process in Pencak Silat, which consists of three stages: the opening ceremony, intensive training, and the closing ceremony. The research also identified many symbols in Pencak Silat, such as spoken words embodied in movements, shouts, and musical accompaniment; objects like training uniforms, belts, and protective gear; and bodily movements like horse stances, guarding stances, attacks, training places, and promotion test events. All the symbols found in this research carry significant meanings related to the formation of personal character. These meanings are influenced by moral, social, cultural, and religious values that become the foundation for each person involved directly in Pencak Silat. This study also shows that Pencak Silat is not just a martial art but also a representation of Indonesia’s cultural diversity and identity.